Crescimento econômico e instabilidade no Brasil - Dionísio Dias Carneiro (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 1999)
– Economic stabilization generates conditions, though necessary not sufficient, to sustainable growth. From the 60s onwards, the trade-off between stability and economic growth (recognized nowadays as a temporary one, without contents that could enable it to orientate the economic policy) has been the focus of economic policy in Latin America debates. This old controversy still divides economists and politicians in many countries when analyzing losses in economic development caused by the stabilization efforts. As a result, instability has been acknowledged as a growth inhibitor in Latin America, where only in the 90s the stability values merited political prestige. Quite different from Asia, where this transition of principles has happened, at least, twenty years before. This paper analyses inflation as a symptom of instability and evaluates its effects upon economic development. It also reviews Brazilian economic growth history, identifying domestic factors of instability and the international financial markets effects on the relation between instability and Brazilian economic growth in recent years. Finally, the paper provides a brief examination of the conditions to Brazilian economic retaking, without the resumption of uncertainty that frustrates the perspective of a sustainable economic growth.
Keywords: N16; 330